Risk-adapted starting age of screening for relatives of patients with breast cancer - Mukama, Trasias; Kharazmi, Elham; Xu, Xing; Brenner, Hermann; Fallah, Mahdi (JAMA oncology, 2020)
Breast cancer screening guidelines acknowledge the need for earlier screening for women at increased risk but provide limited guidance for women with a family history of breast cancer. A risk-adapted starting age of screening for relatives of patients with breast cancer may help supplement current screening guidelines. To identify the risk-adapted starting age of breast cancer screening on the basis of a woman’s detailed family history.
November 14, 2019
Gesehen am 05.02.2020